Salat Sunah sebelum Maghrib dalam Mukhtalif al-Hadis - Heriansyah, Dafis; Mauizah, Adzkiya Zayyan; Apriliani, Devi Rizki; Utomo, Sholeh; Almunadi, Almunadi (Jurnal Riset Agama, 2021)
This study aims to determine the law of the sunnah prayer before maghrib. This study uses a qualitative approach through descriptive-analytical methods. The results and discussion of this study indicate that praying sunnah before maghrib is sunnah, but this sunnah is not recommended based on the hadith of Imam Bukhari. This study concludes that performing sunnah prayers before maghrib is allowed but not recommended, scientifically the law is ghairu muakkad. This study recommends to the public and academics to review the mukhtalif of sunnah prayers before maghrib.